Desalination effects on macroalgae (part A): Laboratory-controlled experiments with Dictyota spp. from the Pacific Ocean and Mediterranean Sea - Muñoz, Pamela T.; Rodríguez-Rojas, Fernanda; Celis-Plá, Paula S. M.; López-Marras, Américo; Blanco-Murillo, Fabio; Sola, Iván; Lavergne, Céline; Valenzuela, Fernando; Orrego, Rodrigo; Sánchez-Lizaso, José Luis; Sáez, Claudio A. (Frontiers in Marine Science, 2023)
Desalination brines from direct seawater intake that get discharged to coastal areas may produce stress responses on benthic marine communities, mostly due to its excess salinity, and especially on sessile organisms; in this context, macroalgae have been understudied in desalination ecotoxicological investigations. In this study, we assessed the short- and long-term cellular tolerance responses in two brown species of the macroalgae genus Dictyota through controlled laboratory conditions. Dictyota kunthii was collected from the eastern Pacific Ocean (average salinity, 34 psu), whereas Dictyota dichotoma was from the Mediterranean Sea (average salinity, 37 psu). Each macroalgae species was exposed for up to 7 days to two conditions with increased salinity values: +2 and +7 psu above their natural average salinity. Photosynthetic parameters and oxidative stress measurements were determined. The results showed that, in both Dictyota species, high salinity values induced reduced photoinhibition (Fv/Fm) but increased the primary productivity (ETRmax) and light requirement (EkETR) especially after 7 days. Conversely, the photosynthetic efficiency (αETR) decreased in hypersalinity treatments in D. dichotoma, while there were no changes in D. kunthii. The reactive oxygen species hydrogen peroxide (H2O2) was greater at high salinity values at 3 days for D. dichotoma and after 7 days in D. kunthii, while lipid peroxidation decreases under hypersalinity with time in both species. Despite the evident H2O2 accumulation in both species against hypersalinity, it did not produce oxidative damage and important impairment in the photosynthetic apparatus. These results contribute to understanding the tolerance strategies at the cellular level of Dictyota spp., which may be considered as potential candidates for biomonitoring of desalination impacts in the field.